Índice de Desenvolvimento Como Liberdade. Uma Proposta Teórico-Metodológica de Análise - Sarah Farias Andrade (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2016)
This work aims to discuss and outline a development index based on the concept of instrumental freedoms of Amartya Sen (2010), called here IDL. The main objective, develops a theoretical and methodological construction, from the perspective of instrumental freedoms of Amartya Sen to review the development. Specifically, we identify the relevant variables and measurement instruments; It proposes a mathematical formula for calculating the development index as freedom taking as reference the Brazilian reality. The theoretical references of this study were structured considering the theoretical approaches to the development, from the perspective of classical liberal school, and specifically in utilitarian thought. They add also the studies on development indicators to support the methodological approach developed here. The IDL is structured on the concept of freedom, being built from five indicators present in the work of Amartya Sen: Political Freedoms (LP), Economic Cash (DE), Social Opportunities (OS), Transparency Guarantees (GT), and Security Protective (SP). Overall, the analysis of instrumental freedoms in the Brazilian context notes that the 1988 Constitution constitutes a relevant legal framework in advance of regional development. However, the partial failure of some constitutional provisions is associated with relative deprivation of human capabilities.